Bulletin 83 The Humidity of Mine Air - R. Y. Williams (The National Institute for Occupational Safety and Health (NIOSH), 1914)
The investigative work described in this report was undertaken by the Bureau of Mines under a cooperative agreement with the department of mining engineering of the University of Illinois and the Illinois State Geological Survey." The purpose of this agreement was to provide for a comprehensive investigation of coal-mining conditions in the State, with especial reference to the possibility of lessening waste in the mining and preparation of coal and of reducing the dangers to which miners are exposed. The Bureau of Mines paid particular attention to those phases of the investigation that were of general interest from their bearing on safety and efficiency in the coal-mining industry as a whole. Thus, it studied the occurrence of gas (methane) in the mines of the southern part of the State," tested the inflammability of the coal dust from many mines, examined the efficiency of the control of ventilating currents, and investigated the factors affecting the humidity of mine air with respect to their bearing on the occurrence of mine explosions. Following the establishment of the fact that under certain conditions dry bituminous coal dust is inflammable, there arose the problem of finding efficient methods of preventing or limiting coal-dust explosions. Experiments in the gas-and-dust gallery at the Pittsburgh testing station of the Bureau of Mines verified the fact that certain dusts that explode violently when dry are rendered inert by proper humidi- .fication of the atmosphere within the gallery, and the importance of humidity as a factor in limiting the inflammability of coal dust in a mine is demonstrated by the fact that there has never been in Illinois a dust explosion during the summer months, whereas the records show a number of dust explosions during cold weather. It is easy to see that the warm moisture-laden air that enters a mine in the summer must deposit moisture on cooling, whereas the cold and relatively dry air that enters in winter must take up moisture as it becomes heated in traveling through the mine.